2010
DOI: 10.1371/journal.pone.0011582
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Colour: A Comparison of Structural, Melanin- and Carotenoid-Based Plumage Colours

Abstract: BackgroundPlumage coloration is important for bird communication, most notably in sexual signalling. Colour is often considered a good quality indicator, and the expression of exaggerated colours may depend on individual condition during moult. After moult, plumage coloration has been deemed fixed due to the fact that feathers are dead structures. Still, many plumage colours change after moult, although whether this affects signalling has not been sufficiently assessed.Methodology/Principal FindingsWe studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 56 publications
7
59
2
Order By: Relevance
“…Feathers are passive structures and variation in their coloration is due to pigment composition and concentration, which reflects the type and quantity of carotenoids ingested during moult (Hill and McGraw, 2006;Peters et al, 2007). Feather coloration may also change after moult (Galván and Sanz, 2006;Delhey et al, 2010). Few studies have explored variation in carotenoid-based colour after moult (Hill and McGraw, 2006;Peters et al, 2008;Delhey et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Feathers are passive structures and variation in their coloration is due to pigment composition and concentration, which reflects the type and quantity of carotenoids ingested during moult (Hill and McGraw, 2006;Peters et al, 2007). Feather coloration may also change after moult (Galván and Sanz, 2006;Delhey et al, 2010). Few studies have explored variation in carotenoid-based colour after moult (Hill and McGraw, 2006;Peters et al, 2008;Delhey et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Feather coloration may also change after moult (Galván and Sanz, 2006;Delhey et al, 2010). Few studies have explored variation in carotenoid-based colour after moult (Hill and McGraw, 2006;Peters et al, 2008;Delhey et al, 2010). Previous studies have experimentally shown that feathers exposed to sunlight become less yellow (Surmacki, 2008;Surmacki et al, 2011) probably due to an effect of pigment oxidation caused by photon absorption.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…by microbial activity, physical damage, UV exposure) progressively exposes embedded carotenoids to additional oxidization, and thus produces colour change despite the lack of additional pigment input [17][18][19][20][21]. An important discovery is that different carotenoid types within a feather have different potential for UV and oxygen modification, with some carotenoids remaining remarkably stable once deposited in feathers whereas others change readily, considerably modifying the appearance of the plumage [20][21][22]. The biochemical stability of carotenoids typically increases with metabolic modification [23,24], including those commonly accomplished by birds [25].…”
Section: Introductionmentioning
confidence: 99%